Aspek Manajemen - Hajijah, Humairah; Hanafi, Muhammad; Yunni, Yunni (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Management is a process or framework that involves guiding or directing a group towards organizational goals such as implementing and evaluating conceptualized planning strategies so that their implementation is in accordance with the direction. This study uses a library research approach or literature study method, namely conducting research on data collected from several sources in the form of books and previous journal publications that are related to management aspects. The purpose of this management aspect study is to determine whether business activities and implementation can be planned, implemented so that the business plan can be declared feasible or otherwise not feasible.